Disadvantageous Socioeconomic Position at Specific Life Periods May Contribute to Prostate Cancer Risk and Aggressiveness - Madathil, Sreenath; Blaser, Christine; Nicolau, Belinda; Richard, Hugues; Parent, Marie-Élise (Frontiers in Oncology, 2018)
Background: Previous studies on socioeconomic position (SEP) and risk of prostate cancer (PCa) have produced contradictory results. Most measured SEP only once during the individuals’ life span. The aim of the study was to identify life course models that describe best the relationship between SEP measured during childhood/adolescence, early- and late-adulthood, and risk of PCa overall as well as according to tumour aggressiveness at diagnosis. Methods: We used data from a population-based case-control study of PCa conducted in the predominantly French-speaking population in Montreal, Canada. Cases (n=1930) with new, histologically-confirmed PCa were ascertained across hospitals deserving the French-speaking population in 2005-2009. Controls (n=1991), selected from Quebec’s list of French-speaking electors, were frequency-matched to cases (±5 years). In-person interviews collected information on socio-demographic and lifestyle characteristics, and a complete occupational history. Measures of SEP during childhood/adolescence included parents’ ownership of a car and father’s longest occupation, while the subject’s first and longest occupations were used to indicate early- and late-adulthood SEP, respectively. We used the Bayesian relevant life course exposure model to investigate the relationship between lifelong SEP and PCa risk. Results: Cumulative exposure to disadvantageous SEP was associated with about a 50% increase in odds of developing PCa. Late-adulthood SEP was identified as a sensitive period for aggressive PCa. Childhood/adolescence SEP based on parents’ ownership of a car was associated with non-aggressive PCa. Associations were independent from PCa screening. Conclusion: Disadvantageous SEP over the life course was associated with higher PCa incidence, with consistent evidence of sensitive time periods for cancer aggressiveness. The mechanisms through which disadvantageous SEP relates to PCa risk need to be further elucidated.